1991
DOI: 10.1159/000243315
|View full text |Cite
|
Sign up to set email alerts
|

Development of Urea-Synthesizing Capacity in Preterm Infants during the First Weeks of Life

Abstract: The urea-synthesizing capacity of the liver was studied in 20 healthy preterm infants during the first month of life. The urea-synthesizing capacity was estimated by the ratio of 15N abundances of ammonia and urea in the 6-hour urine after administration of 3 mg 15N-labelled ammonium chloride/kg body weight. The ratio increases with increasing protein intakes from the 2nd to the 3rd week of life. On protein intakes of more than 3 g/kg/ day from the 3rd week to the end of the 2nd month of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

1996
1996
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 7 publications
1
15
1
Order By: Relevance
“…In previous studies, we could show that the quotient of 15 N excess abundance of 15 Nammonia and 15 N-urea in urine after application of 15 N-ammonia as tracer reflect urea synthesis [13][14][15]. In the present study, we used this 15 N-ammonia test to investigate the possible influence of IUGR and prematurity on the postnatal develoment of the urea-synthesizing capacity during the first weeks of postnatal life.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…In previous studies, we could show that the quotient of 15 N excess abundance of 15 Nammonia and 15 N-urea in urine after application of 15 N-ammonia as tracer reflect urea synthesis [13][14][15]. In the present study, we used this 15 N-ammonia test to investigate the possible influence of IUGR and prematurity on the postnatal develoment of the urea-synthesizing capacity during the first weeks of postnatal life.…”
Section: Introductionmentioning
confidence: 92%
“…In infants with IUGR we found a higher urinary ammonium excretion and a lower urea excretion when compared to infants with similar postnatal age but without IUGR [10]. After application of 15 N-glycine, Van Coudoever et al [11] found a very low 15 N enrichment of urinary urea in preterm infants with IUGR; even the nitrogen balance was high when compared to preterm infants without IUGR. In contrast, Kalhan [12] could not find any influence of IUGR on the urea synthesis rate in term infants.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Nothing thus far seems to be published either about ammonium ion intake or the amount of ammonium ion produced in the intestine and how this varies with the infant's age. It is known, however, that the daily urine excretion of ammonium ion markedly decreases during the course of the first 6 weeks of life, at the same time as the urine excretion of urea increases (69,70,71). At the age of 6 weeks the normal infant excretes 0.5-1 mmol ammonidammonium ions daily in the urine (69), an amount of ammonium ion which can be regarded as a safety margin which, if needed, at least partly can be used for neutralising excess bicarbonate ions.…”
Section: Dysfunction In the System -Does It Exist?mentioning
confidence: 99%